STRATEGIC URBAN PLANNING AND LANDSCAPE INFRASTRUCTURE INTEGRATION: A THEORETICAL MODEL FOR SUSTAINABLE URBAN DEVELOPMENT IN HOT CLIMATES, CASABLANCA AS A CASE STUDY - Al echcheikh, El Alaoui Douaa (SWorldJournal, 2024)
This article introduces a theoretical model developed specifically for sustainable urban planning in hot climates, where challenges such as extreme temperatures, water scarcity, and rapid urbanization place unique demands on the built environment. The mod